2011
DOI: 10.1002/jsfa.4322
|View full text |Cite
|
Sign up to set email alerts
|

Purification, cloning, expression and immunological analysis of Scylla serrata arginine kinase, the crab allergen

Abstract: Both of purified nAK and rAK reacted positively with sera from subjects with crustacean allergy in immunoblotting and GICA analysis, indicating AK is a common allergen of mud crab. In vitro expressed AK is proposed as a source of the protein for immunological or clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…In recent years, other proteins in shellfish, such as myosin light chain, sarcoplasmic calcium-binding protein, troponin C, and triosephosphate isomerase, have been identified as novel allergenic proteins (Bauermeister et al, 2011). The 40-kDa arginine kinase (AK) from the shrimps Penaeus monodon (Yu et al, 2003) and Penaeus (Litopenaeus) vannamei (Garcia-Orozco et al, 2007) and from the Indo-Pacific swamp crab Scylla serrata (Shen et al, 2011) has also been identified as an important allergen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, other proteins in shellfish, such as myosin light chain, sarcoplasmic calcium-binding protein, troponin C, and triosephosphate isomerase, have been identified as novel allergenic proteins (Bauermeister et al, 2011). The 40-kDa arginine kinase (AK) from the shrimps Penaeus monodon (Yu et al, 2003) and Penaeus (Litopenaeus) vannamei (Garcia-Orozco et al, 2007) and from the Indo-Pacific swamp crab Scylla serrata (Shen et al, 2011) has also been identified as an important allergen.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that AK is specifically recognized by IgE collected from crab-sensitized allergic patients (Shen et al, 2011), and have defined two areas of S. paramamosain AK (amino acids 174-181 and 253-256) as the main epitope regions of the protein. Further serological assays of synthetic peptides defined three experimental linear epitopes (amino acids 127-141, 141-155, and 211-225) .…”
Section: Introductionmentioning
confidence: 99%
“…Several AKs were cloned or identified from other crustaceans (Arockiaraj et al, 2011;Shen et al, 2011;Chen et al, 2013;Xie et al, 2014). In this study, an AK gene was cloned from D. magna with an ORF of 1074 bp encoding for 357 AA.…”
Section: Discussionmentioning
confidence: 99%
“…AK was recently reported as an allergen in different crustacean species which was identified in white shrimp (Litopenaeus vannamei) (García-Orozco et al, 2007), gulf shrimp (Penaeus aztecus) (France et al, 1997), chinese shrimp (Fenneropenaeus chinensis) ( Y a o et al, 2005), black tiger prawn (Penaeus monodon) and other shrimp species using a proteomics approach (Abdel Rahman et al, 2010a;Yu et al, 2003). Moreover, AK has been identified in other crab species: mud crab (Scylla serrata) (Shen et al, 2011), and by our group in snow crab (Chionoecetes opilio) (Abdel Rahman et al, 2011), where 49% of the participant patient's sera have a reactivity with AK. Arginine kinase also has been reported is allergen in some other invertebrates, such as the house dust mite (Dermatophagoides farinae) (Bi & Chew, 2004), Indian-meal moth (Plodia interpunctella) (Binder et al, 2001), and silkworm larvae (Bombyx mori) (Liu et al, 2009).…”
Section: Shellfish Allergensmentioning
confidence: 99%
“…Allergen analysis by MS started by determining the molecular weight of small allergens such as parvalbumin (12 kDa) in fish (Bugajska-Schretter et al, 2000;Cai et al, 2010;Swoboda et al, 2002). After completing the genome sequence and developing the MS-interface databases, some studies use the PMF approach to identify the seafood allergens evaluated by immunoblotting (Ayuso et al, 2009;García-Orozco et al, 2007;Mazzeo et al, 2008;Shen et al, 2011;Yamasaki et al, 2010;Yu et al, 2003). The best example of this kind of research was in 2003, when Pen m 2 shrimp allergen was identified using PMF, where the recognized spot proteins by a pool of patients' sera were tryptic digested and analyzed by MALDI-ToF (Yu et al, 2003).…”
Section: Characterization Of Seafood Allergen Using Mass Spectrometrymentioning
confidence: 99%